Epileptiform Activity and Cognitive Deficits in SNAP-25+/− Mice are Normalized by Antiepileptic Drugs. (12th October 2012) - Corradini, Irene; Donzelli, Andrea; Antonucci, Flavia; Welzl, Hans; Loos, Maarten; Martucci, Roberta; De Astis, Silvia; Pattini, Linda; Inverardi, Francesca; Wolfer, David; Caleo, Matteo; Bozzi, Yuri; et al.
Abstract : Synaptosomal-associated protein of 25 kDa (SNAP-25) is a protein that participates in the regulation of synaptic vesicle exocytosis through the formation of the soluble NSF attachment protein receptor complex and modulates voltage-gated calcium channels activity. The Snap25 gene has been associated with schizophrenia, attention deficit hyperactivity disorder, and bipolar disorder, and lower levels of SNAP-25 have been described in patients with schizophrenia. We used SNAP-25 heterozygous (SNAP-25 +/− ) mice to investigate at which extent the reduction of the protein levels affects neuronal network function and mouse behavior. As interactions of genotype with the specific laboratory conditions may impact behavioral results, the study was performed through a multilaboratory study in which behavioral tests were replicated in at least 2 of 3 distinct European laboratories. Reductions of SNAP-25 levels were associated with a moderate hyperactivity, which disappeared in the adult animals, and with impaired associative learning and memory. Electroencephalographic recordings revealed the occurrence of frequent spikes, suggesting a diffuse network hyperexcitability. Consistently, SNAP-25 +/− mice displayed higher susceptibility to kainate-induced seizures, paralleled by degeneration of hilar neurons. Notably, both EEG profile and cognitive defects were improved by antiepileptic drugs. These results indicate that reduction of SNAP-25 expression is associated to generation of epileptiform discharges and cognitive dysfunctions, which can be effectively treated by antiepileptic drugs.